Viscose and thrombocytic-aggregation disorders on patients with myocardial infarction with stable elementation of ST segment - Uzun, Dmitriy U.; Lazoryshynets, Vasyl V.; Uzun, Katerina S. (Annals of Mechnikov's Institute, 2021)
Clinical studies indicate a significant role in the pathogenesis of acute myocardial infarction, the functional state of platelet aggregation and blood viscosity, which determine the nature of blood flow in the vessels at the level of macro– and microcirculation. The aim of the study was to analyze changes in viscosity and platelet-aggregation disorders under the influence of different tactical, diagnostic and interventional approaches in patients with myocardial infarction and stable elevation of the ST segment in the presence of multivascular coronary artery disease. The study used 4 tactical and treatment-diagnostic approaches during the year of observation. Patients with myocardial infarction with persistent ST-segment elevation were found to have hyperviscosity and hypercoagulability syndromes, manifested in the first weeks by a compensatory increase in platelet count, blood viscosity, fibrinogen levels, and an increase in platelet aggregation. Carrying out additional in-depth examination of coronary circulation (coherent tomography and intravascular sonography) as the main methods of detailed assessment of atheromatous process and further application of delayed stenting of infarct-independent arteries in group 1, contributed to lower amplitude of fluctuations, due to the systemic step-by-step improvement of arterial blood supply, to optimize the state of viscosity and processes of adhesion / aggregation of platelets. Traditional tactical and medical-diagnostic principles of this category of patients do not allow to fundamentally improve the state of viscosity and coagulation-aggregation parameters, even with the use of dual antiplatelet therapy. DOI: 10.5281/zenodo.5499580